Systematic Literature Review: Penerapan Layanan Konseling Kelompok Solution Focused Brief Therapy (SFBT) pada Peserta Didik di Sekolah Menengah - Dartina, Vina; Nabila, Syifa; Alfaiz, Alfaiz; Maharani, Iris Fatia (Indonesian Journal of Educational Counseling, 2024)
The era of disruption due to the pandemic has caused a decline in the mental condition of students, especially in secondary schools. Efforts to overcome this problem include implementing guidance and counseling services in schools, one of which is group counseling. The study aims to determine how the application of group counseling services with a Solution Focused Brief Therapy (SFBT) approach to students in secondary school (adolescents) which includes the understanding of SFBT group counseling, the scope of problems overcome, the procedure for implementing and the success of SFBT group counseling as an alternative to counseling that is considered to meet the needs of generation Z students. Systematic Literature Review (SLR). Data collection using documentation techniques. The amount of literature studied after data selection amounted to 21 literatures. The data analysis used is content analysis. The results revealed that the application of SFBT group counseling is a short therapeutic focusing on solutions because it can be done with 4 to 8 sessions with a duration of 40 to 70 minutes and the counseling process does not well on problems but focuses on awareness and the ability of counsellors to solve problems. SFBT group counseling has been proven effective in various problems as well as the development of students in secondary schools covering the fields of Guidance Counseling services, namely personal, social, academic and career.